Computational chemistry : reviews of current trends - Leszczynski, Jerzy, 1949- (Computational Chemistry: Reviews of Current Trends., 1999)
A blend of methodological and applied contributions on computational chemistry. It explores research results and the topographical features of several molecular scalar fields. A discussion of topographical concepts is followed by examples of their application to several branches of chemistry.